Adam Watkins' 4th Grade Manchester-Gate Class Tour of Fresno Bee Facility at 1921 E Street, Fresno - Watkins, Howard::::::::: (1987)
Ron Orozco near mailroom where completed Fresno Bee newspaper would spiral down for delivery Teacher David Berklich, in long sleeve white shirt